A robot for handling hazardous chemical. - Aris, Ishak; Teh, Jenny Cheng Choo; Koh , Johnny Siaw Paw (2007)

(untitled)
The main purpose of this invention is to provide a robotic system that is capable of handling hazardous chemical processing and experiments at laboratories. It can be reprogrammed to perform various tasks with flexible degrees of freedom. It can be used in laboratories, chemical factories and hospitals. This system is also known as the Robolab. The main structure of the Robolab can be divided into software and hardware parts. The software is responsible to drive the robotic arms in order to move to a precise position and at the same time control the inputs and outputs devices of the system. The program consists of various functions such as home routine, reset routine, process routine, jog routine and etc. Meanwhile the hardware of the Robolab system can be divided into special dedicated modules such as a positioning module, a gripper module, a sensing module, a product placement module and etc. Basically the Robolab system consists of a personal computer, motion controller, input and output devices, actuators and mechanical robotic arms. A personal computer is needed to download program into the EPROM of the motion controller through the connection of RS232 host link system. The motion controller acts as the main processor of the robotic system. The actuators are used to drive the mechanical robotic arms. This robot also has a built-in fault detection system. It will inform its main controller if any particular faults occur to the system.